Performance of transportation network under perturbations: Reliability, vulnerability, and resilience - Gu, Yu; Fu, Xiao; Liu, Zhiyuan; Xu, Xiangdong; Chen, Anthony (Transportation research. Part E, Logistics and transportation review, 2020)
•Review recent studies on reliability, vulnerability, and resilience of transportation network.•Definitions, quantitative indices, and analyses of the three concepts are overviewed.•The characteristics of, and the relationship among the three concepts are investigated.•We provide remarks on the foci, measurements, and applications of the three concepts. We review recent studies on transportation network performance under perturbations. Three representative concepts relating to network performance are covered: reliability, vulnerability, and resilience. With an overview of the definitions and the quantitative indices of these three concepts, we analyse and compare their similarities and differences in the context of transportation. These concepts differ from each other in terms of focus, measurement, and application scenario. Numerical examples are conducted to assess these concepts under different perturbation scenarios. The results indicate their rationale in reflecting network performance under perturbations, yet their outputs differ. Moreover, the relationship among the three concepts is intuitively illustrated by the analysis results.